Time-Driven Activity-Based Costing: designing a model in a Portuguese production environment - Barros, R. S.; Ferreira, A. (Qualitative Research in Accounting and Management, 2017)
Purpose: By designing a pilot Time-Driven Activity-Based Costing (TDABC) model, this study seeks to examine in depth the suitability and the complexity of TDABC in a manufacturing company. Design/Methodology/Approach: To obtain a deeper understanding on the matters to analyse, this research adopts an interventionist approach. The host organisation is GP, a Portuguese company in the frozen food sector. Findings: Our experience allows us to assert that TDABC is suitable for a manufacturing company and it is able to deal with the variability of the industrial processes. Nonetheless, through a comparison with the models presented in the literature, TDABC appears to be more complex for manufacturing. We argue that this happens for two reasons: First, the two types of resources (human labour and machinery) used in production areas create a need to split tasks and to create two equations for each process, something that does not happen in service companies. Second, times are difficult to individualise for certain highly automated procedures, which could also give rise to some errors. Research limitations/implications: The designed model is compared to other models presented in the literature. Practical implications: This study shows a real example of TDABC in manufacturing and the procedural innovation of the time equations. Originality/Value: Since the TDABC literature has been mostly focused on examples of service companies, we examine the technical suitability and the complexity of TDABC in manufacturing companies.